Chemical Characterization, Antioxidant and Antibacterial Activity of Essential Oil of Cymbopogon winterianus Jowitt (Citronella) from Western Nepal - Shrestha, Dipesh; Sharma, Prabha; Pandey, Anisha; Dhakal, Kamal; Baral, Ram P.; Adhikari, Achyut (Current Biotechnology, 2022)
Background: Essential oils (EOs) are a mixture of volatile compounds of plant origin, which possess substantial biological activities such as antioxidant, antimicrobial, and antifungal activity. Objective: This study aimed to determine the chemical composition, antioxidant, and antibacterial activity of essential oil isolated from Cymbopogon winterianus Jowitt. Methods: The hydro-distillation method was used for the isolation of essential oil. The chemical composition of the isolated essential oil was analyzed using the gas chromatography/mass spectrometry (GC-MS) technique. Antioxidant activity was determined using a 2,2-diphenyl-1- picrylhydrazyl (DPPH) free radical scavenging assay, and the IC50 value was calculated. The welldiffusion method was applied for the antibacterial activity, and the zone of inhibition (ZOI) was measured. Results: The essential oil from Cymbopogon winterianus Jowitt was isolated with a 0.5% yield. Gas Chromatography-Mass Spectrometry(GC-MS) analysis reported 19 different compounds, out of which, Geraniol (28.87%), Citronellal (11.85%), Citronellol (10.88%), Geranial (9.19%), trans- Geranyl acetate (9.11%), and Neral (8.02%) were found to be the major constituents. The essential oil was a promising antioxidant with an IC50 value of 0.458±0.39μg/mL compared to the standard Quercetin of 1.187±0.22μg/mL. In addition, the isolated essential oil revealed antibacterial activity against Staphylococcus aureus (ZOI=13.2mm), Bacillus subtilis (ZOI=9.9mm), and Enterococcus faecalis (ZOI=8.4mm). Conclusion: The essential oil isolated from Cymbopogon winterianus Jowitt exhibits antioxidant and antibacterial activity, implying that it could find use in modern medicine.
Keywords: antioxidant